The Semiotic Of Reba Ceremony In Mangulewa Village - Helena Anjelina Anu; Rikardus Nasa; Nur Syamsiyah Ekhsan (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2024)
This research discusses the semiotic of Reba ceremony in Mangulewa village. This research has three objectives, namely, (1) describe the process of Reba ceremony, (2) explain the meaning of every stage of Reba ceremony, (3) find out the meaning of signs or symbols and poetry that are used in Reba ceremony. This research used qualitative methods with three data collection techniques, namely observation, interview and, documentation. The results of this study show the following, (1) there are three stages implementation of Reba, namely preparation stage, core stage, and closing stage (2) there is a meaning contained in every stage of Reba ceremony namely, (a) the preparation stage there is wasi loka lanu meaning cleaning and preserving, bui loka means cooking food for the ancestors, (b) the core stage there is kobe dheke means the first night climbing the stairs and entering the traditional house, kobe dhoi means praise/pray to uwi, kobe su'i means a story about the long journey of the ancestors to the land of Ngada, (c) the closing satage is Ire means a prohibition for the Mangulewa community not to work in the garden during the week. (3) The meaning of signs or symbols and poems in the Reba ceremony, (a) signs used in the Reba ceremony, namely uwi, sacrificial animals, su'a uwi, Mataraga, Keka lela, watu lanu, ngadhu, bhaga, (b) poems used in the Reba ceremony ceremony, namely Ti'i ka ebu, fedhi tua, O Uwi, and Su'i Uwi.